(untitled) (Research, Society and Development, 2025)
Chagas disease remains a significant public health challenge in Brazil and has undergone important epidemiological changes in recent decades. Recent studies reveal an increase in acute cases resulting from oral transmission, particularly in the Northern region, associated with the consumption of contaminated foods, as well as the persistence of secondary vectors in endemic areas. Mortality related to Trypanosoma cruzi also remains high in states such as Bahia and Ceará, influenced by delayed diagnosis and limitations in the follow-up of chronic cases. Vulnerable groups—including blood donors, homeless individuals, and rural populations—continue to show a considerable prevalence of infection, reinforcing the need for continuous surveillance strategies. Overall, the analyzed evidence indicates that, despite advances in vector control, the disease maintains heterogeneous distribution and a substantial impact on socially vulnerable populations. These findings highlight the importance of strengthening integrated surveillance, improving preventive actions, and expanding early detection to reduce new cases and Chagas disease–related mortality.